Efficiency of microalgae cultivation automated system: a case study of green algae Chlorella ellipsoidea TISTR 8260 - Sudarat Theerapisit; Somrak Rodjaroen; Siriluk Sintupachee (Penerbit Universiti Kebangsaan Malaysia, 2023)
Microalgae play an important economic role as aquaculture feed. This study aimed to create an automated algae cultivation system with variable light intensity for the culture of Chlorella ellipsoidea strain TISTR 8260. The automated cabinet could work continuously for at least 30 days, with the growth rates of microalgae in culture systems with light intensities of 1000 Lux, 3000 Lux, and 5000 Lux peaking on day 14, whereas the fluorescent control showed peak microalgae growth on day 6. On day 30, the biomass harvested from microalgae grown in 1000 Lux, 3000 Lux, 5000 Lux, and fluorescent control was 0.1935 ± 0.151 mg/L, 0.1996 ± 0.220 mg/L, 0.2041 ± 0.159 mg/L, and 0.0674 ± 0.191 mg/L, respectively, which was not significantly different between the groups but significantly higher than the control (P-value = 0.05, DF = 3, F(3,36) = 7). The automated algae cabinet with a light intensity of 5000 Lux and a rotation speed of 150 r.p.m produced the maximum biomass, which was three times that produced by a fluorescent light source.